ANALISIS DAN OPTIMASI WLAN DENGAN PENDEKATAN PPDIOO - Muhammad Khuzain; Sigit Kusmaryanto; Fakhriy Hario Partiansyah (Jurnal Mahasiswa TEUB, 2020)
High implementation of WLAN technology and poor development planning create many problem in reality. Weak signal strength and interference from neighbor AP can decrease wireless communication performance. In the channel assignment point of view, interference consist of Co-Channel Interference (ACI) and Adjacent Channel Interference (ACI). Optimization is the key to minimize the impact from these problems. In this paper, the author perform WLAN coverage area enhancement using simulated access point (AP). Quality signal like level signal before and after optimization is compared to ensure good performance result. In other side, focus experiment is minimizing impact ACI in fixWLAN network from interference of mWLAN. Due to high mobility and personal use, mWLAN can become great interference sources for fixWLAN. Interference impact reduction performed with physical distance (D) and channel distance (N) controlling. Observation parameter used in this experiment is throughput and packet loss. In conclusion, quality statistic improvement for signal level above -45 dBm in building 1 (1st floor) is 36,8%, in building 1 (2nd floor) is 64,1 %, in building 2 is 23,7 %, in building 3 is 58,1 %, and in building 4 is 86,6 %. In the other side, impact of Adjacent Channel Interference can be reduced by addition physical separation and using high channel separation. The highest performance obtained by experiment is using 5 channel separation and 5 m physical separation with average throughput is 55,2 Mbps and average packet loss is 0,061 %. Index Terms—Adjacent Channel Interference (ACI), Optimization Coverage Area, Packet Loss, Throughput, WLAN